All Days 1993
DOI: 10.4043/7248-ms
|View full text |Cite
|
Sign up to set email alerts
|

Outer Continental Shelf Drilling Blowouts, 1971-1991

Abstract: From 1971 through 1991, 87 blowouts occurred during drilling operations on the Outer Continental Shelf of the United States. During this 21-year period, 21,436 wells were drilled. Eleven of the blowouts resulted in casualties (61 injuries and 25 fatalities). Most of the blowouts were attributable to shallow gas influxes and were of short duration. The overall blowout rate was one per every 246 wells drilled (one per 256 wells drilled if sulfur wells are excluded). The rate for blowouts with casualties and fata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…Results indicated that bridging leading to self-killing may occur only in a small number of situations. This conclusion differed from earlier published data from shallow water Gulf of Mexico Shelf wells which show that self-killing is likely to occur in shallow-hazard gas blowout scenarios [4][5][6][7] .…”
Section: Motivation For the Workcontrasting
confidence: 93%
“…Results indicated that bridging leading to self-killing may occur only in a small number of situations. This conclusion differed from earlier published data from shallow water Gulf of Mexico Shelf wells which show that self-killing is likely to occur in shallow-hazard gas blowout scenarios [4][5][6][7] .…”
Section: Motivation For the Workcontrasting
confidence: 93%
“…Regular trials of the procedures should be undertaken (given live implementation is likely to be infrequent) and adjustments made as necessary. These are the recommendations and ways of solution of some problems: a fatigue management plan, extend exhausts on skimmer power pack to better disperse emissions, the use of satellite sensing technology to support oil spill response, Create a system that involves the chemical matching of the oil slick to samples taken from the suspect vessel to positively identify the polluter [5,6].…”
Section: Fig 2 Suspension Model Diagrammentioning
confidence: 99%
“…The generation of abnormal pressure in the pore spaces happens if a pressure seal (impermeable barrier) is present, and fluids trapped and cannot escape (El-Werr et al 2017). The abnormal pressure must be controlled to prevent dangerous problems such as stuck drill pipes and blowout of wells during drilling operation (Danenberger 1993).…”
Section: Introductionmentioning
confidence: 99%